Preliminary investigation on taxonomic status of sympatric Tylonycteris species in Malaysia - Roberta Chaya Tawie, Tingga; Mohd Ridwan, Abd Rahman; Fatin, N. R. (Malaysian Nature Society, 2020)
Tylonycteris or flat-headed bat is known for its taxonomic complex within this genus. This study attempts to investigate the complexity within Tylonycteris using morphometric approach. The result from 34 morphological characters of hierarchical tree constructed two major groups splitting each respective Tylonycteris species into Malaysia Peninsular and Borneo populations. It is suggested to revise the species name according to type specimen, as proposed by recent previous study. Conservation and taxonomic status of Tylonycteris requires immediate reassessment due to the cryptic nature of these species.